2022
DOI: 10.1029/2021gl097043
|View full text |Cite
|
Sign up to set email alerts
|

Convective and Microphysical Characteristics of Extreme Precipitation Revealed by Multisource Observations Over the Pearl River Delta at Monsoon Coast

Abstract: Extreme precipitation is an issue of worldwide concern, but its microphysics remain elusive. The convective and microphysical characteristics of extreme precipitation features (EPFs) in a monsoon coastal area (South China) are investigated mainly using 2‐year observations from a dual‐polarization radar and distrometers. The EPFs are accompanied by a broad range of convective intensity, and categorized into the “intense”, “moderate”, and “weak” convection accounting for 17.3%, 48.6% and 34.1% of the total popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 63 publications
(92 reference statements)
8
45
1
Order By: Relevance
“…Yu et al. (2022) reported that warm‐rain process is still very important in contributing to extreme precipitation in strong convective systems. Overall, the downward increase of drop size (indicated by reflectivity) below the freezing level of WeEPEs is much greater than that of InEPEs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yu et al. (2022) reported that warm‐rain process is still very important in contributing to extreme precipitation in strong convective systems. Overall, the downward increase of drop size (indicated by reflectivity) below the freezing level of WeEPEs is much greater than that of InEPEs.…”
Section: Resultsmentioning
confidence: 99%
“…Some extreme rainfall events are accompanied by relatively warm cloud tops, lower radar echo tops, and little lightning activity (Gochis et al., 2015; Petersen, Carey, et al., 1999; Rasmussen & Houze, 2012; Smith et al., 2000; Tsuji et al., 2020). Also, warm‐type rain or relatively weak convection contributes a significant fraction of heavy rainfall over certain regions, for example, the Korean Peninsula (Sohn et al., 2013), Japan (Hamada & Takayabu, 2018) and Pearl River Delta in southern China (Yu et al., 2022). Such kind of storms occur over land in mid‐latitudes infrequently, but when they do occur, they can be devastating (Petersen, Carey, et al., 1999; Zipser & Liu, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent dual polarization upgrade of the operational weather radars in coastal South China has provided an opportunity to analyze the microphysical characteristics of precipitation over the coastal areas of South China, such as the rainband of Typhoon Nida [43], two consecutive mesoscale convective systems (MCSs) leading to a maximal rainfall accumulation of 451 mm on 11 May 2014 [29], the record-breaking rainfall event of 7 May 2017 influencing the megacity of Guangzhou [37], and an early summer event with coexisting frontal and warm-sector heavy rainfall [44]. Two case studies [29,37] and a statistical analysis focusing on extreme precipitation over coastal South China [45] consistently suggested that the extreme precipitation could be accompanied by a variety of convective intensities (i.e., the strength of mixed-phase processes) ranging from weak to intense, and has much more populous raindrops than the "continental" regime with a mean size larger than the "maritime" regime. However, the understanding of microphysical processes leading to the generation of extreme precipitation worldwide is still far from complete.…”
Section: Introductionmentioning
confidence: 99%